2014
DOI: 10.1002/asia.201402233
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Investigation of the Ring‐Expansion Reaction of N‐Heterocyclic Carbenes with an Iminoborane Dihydride

Abstract: Conversions of iminoboranes with an N-heterocyclic carbene (NHC) result in borane dihydride formation (BDF) concomitant with dihydrogenated NHC. The iminoborane dihydrides are prone to a hydride-mediated ring-expansion reaction (RER) at elevated temperature, that is, the insertion of the boron atom into the adjacent CN bond of the NHC to yield boracycles. Upon conversion of a saturated-backbone NHC with respective iminoborane precursors RER yet occurs at ambient temperature to yield the ring-expanded products… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
43
0
7

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 43 publications
3
43
0
7
Order By: Relevance
“…4), where ring insertion requires migration of at least one methyl group to the carbenic carbon, it is found that the favoured pathway involves initial hydride migration (T1) followed by ring expansion (T2) and a final methyl migration (T3). 5,6 Trends in the T1 barriers (H migration) for HBMe 2 are similar to that of Ph 2 SiH 2 and H 2 BMe, being lowest for 2 (74 kJ mol −1 ) and 5 (105 kJ mol −1 ), with the other three NHCs having higher barriers of 132 to 150 kJ mol −1 . The preference for hydride migration has been consistently predicted by theoretical studies, [9][10][11][12][13] and also observed experimentally.…”
Section: Boranesmentioning
confidence: 59%
See 2 more Smart Citations
“…4), where ring insertion requires migration of at least one methyl group to the carbenic carbon, it is found that the favoured pathway involves initial hydride migration (T1) followed by ring expansion (T2) and a final methyl migration (T3). 5,6 Trends in the T1 barriers (H migration) for HBMe 2 are similar to that of Ph 2 SiH 2 and H 2 BMe, being lowest for 2 (74 kJ mol −1 ) and 5 (105 kJ mol −1 ), with the other three NHCs having higher barriers of 132 to 150 kJ mol −1 . The preference for hydride migration has been consistently predicted by theoretical studies, [9][10][11][12][13] and also observed experimentally.…”
Section: Boranesmentioning
confidence: 59%
“…1 Despite NHCs being considered to be robust spectator ligands in catalysis, the activation of C-N bonds has significant generality, being thus far observed for the elements Be, 2 B, [3][4][5] Si, 6 Ni, 7 and Zn. 1 Despite NHCs being considered to be robust spectator ligands in catalysis, the activation of C-N bonds has significant generality, being thus far observed for the elements Be, 2 B, [3][4][5] Si, 6 Ni, 7 and Zn.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this dehydrogenative redox process, the tellurium atom is further reduced to the −2 oxidation state with concomitant formation of dihydrogenated NHC (L Et (H 2 ), hydrogenated at the formerly carbenoid atom). The abstraction of hydrogen from iminoboranes using NHC to produce NHC(H 2 ) had been previously investigated25.…”
Section: Resultsmentioning
confidence: 99%
“…303 The ring expansion of іmіdazol-2-ylіdenes is also effected by other Lewis acids, particularly boranes 304 and amіnoboranes. 305,306 These result in the formation of borazines of types 67D,E, along with boroxoles 68B (Scheme 68). 307 A beryllium analogue 308 of the silazines 67C, compound 67F (Scheme 67), is also known.…”
mentioning
confidence: 99%